Encounters with Popular Pasts
IX, 253 p. 47 illus., 46 illus. in color.
Keywords: This volume is based on the recognition that heritage is popular and popular culture is now readily transformed into heritage, whose meanings and myths reshape social life and political and economic realities, as well as re-make “tradition”. The papers in this volume consider: What does popular heritage look like? To whom does it speak? Is it active in dissolving class and cultural boundaries or just in reproducing new ones? How do societies manage a heritage that is fluid, immediate and that straddles extremes of serious conflict and hedonistic frivolity? When and under what circumstances is the creation and expression of new cultural forms – popular culture – capable of being transformed into heritage?